The types Figurative Language in Michel Jackson song lyrics - I Kadek Agus Kumara Putra; Ni Wayan Suastini (CV. Multi Kreasi Media, 2022)
In this study, the varieties of figurative language will be identified and analyzed in the lyrics of Michel Jackson songs. In this study, were analyzed using Davis (2016) theory to determine the types of figurative languages. This study employed a qualitative methodology. This research led to the discovery of 3 differentforms of most figurative language in song lyrics for the study. They consist of Metaphor (3), Simile (5), Hyperbole (3). In this result found most types figurative language that is simile. And the writer hope that this article could help readers to understand the classification of types figurative language.